Time-dependent facilitation of homologous actions - Raphael Hamel; Felix-Antoine Savoie; David Punt; Ned Jenkinson; Mark R. Hinder (Experimental Brain Research, 2026)

Performance on the balloon analogue risk task and anticipatory response inhibition task is associated with severity of impulse control behaviours in people with Parkinson’s disease - Alison Hall; Matthew Weightman; Ned Jenkinson; Hayley J. MacDonald (Experimental Brain Research, 2023)
Dopamine agonist medication is one of the largest risk factors for development of problematic impulse control behaviours (ICBs) in people with Parkinson’s disease. The present study investigated the potential of dopamine gene profiling and individual performance on impulse control tasks to explain ICB severity. Clinical, genetic and task performance data were entered into a mixed-effects linear regression model for people with Parkinson’s disease taking (n = 50) or not taking (n = 25) dopamine agonist medication. Severity of ICBs was captured via the Questionnaire for Impulsive-compulsive disorders in Parkinson’s disease Rating Scale. A cumulative dopamine genetic risk score (DGRS) was calculated for each participant from variance in five dopamine-regulating genes. Objective measures of impulsive action and impulsive choice were measured on the Anticipatory Response Inhibition Task and Balloon Analogue Risk Task, respectively. For participants on dopamine agonist medication, task performance reflecting greater impulsive choice (p = 0.014), and to a trend level greater impulsive action (p = 0.056), as well as a longer history of DA medication (p < 0.001) all predicted increased ICB severity. DGRS however, did not predict ICB severity (p = 0.708). No variables could explain ICB severity in the non-agonist group. Our task-derived measures of impulse control have the potential to predict ICB severity in people with Parkinson’s and warrant further investigation to determine whether they can be used to monitor ICB changes over time. The DGRS appears better suited to predicting the incidence, rather than severity, of ICBs on agonist medication.

Exploring stop signal reaction time over two sessions of the anticipatory response inhibition task - Alison Hall; Ned Jenkinson; Hayley J. MacDonald (Experimental Brain Research, 2022)
Various behavioural tasks measure response inhibition encompassing the ability to cancel unwanted actions, evaluated via stop signal reaction time (SSRT). It is unclear whether SSRT is an unchangeable inherent measure of inhibitory network integrity or whether it can improve with repetition. The current study explored if and how SSRT changed over two sessions for the Anticipatory Response Inhibition Task (ARIT), and how this compared with the Stop Signal Task (SST). Forty-four participants repeated the ARIT and SST over two sessions. SSRT and its constituent measures (Go trial reaction time, stop signal delay) were calculated. SSRT reflecting non-selective response inhibition was consistent between sessions in the ARIT and SST (both p > 0.293). Reaction time and stop signal delay also remained stable across sessions in the ARIT (all p > 0.063), whereas in the SST, reaction time ( p = 0.013) and stop signal delay ( p = 0.009) increased. SSRT reflecting behaviourally selective stopping on the ARIT improved ( p < 0.001) over two sessions, which was underpinned by changes to reaction time ( p < 0.001) and stop signal delay ( p < 0.001). Overall, the maximal efficiency of non-selective inhibition remained stable across two sessions in the ARIT. Results of the SST confirmed that non-selective inhibition can, however, be affected by more than inhibitory network integrity. Behaviourally selective stopping on the ARIT changed across sessions, suggesting the sequential neural process captured by the SSRT occurred more quickly in session two. These findings have implications for future studies that necessitate behavioural measures over multiple sessions.

Paradoxical facilitation after depotentiation protocol can precede dyskinesia onset in early Parkinson’s disease - Angel Lago-Rodriguez; Viviana Ponzo; Ned Jenkinson; Sonia Benitez-Rivero; Miguel Fernandez Del-Olmo; Michele Hu; Giacomo Koch; Binith Cheeran (Experimental Brain Research, 2016)

The effect of BDNF val66met polymorphism on visuomotor adaptation - Raed A. Joundi; Virginia Lopez-Alonso; Angel Lago; John-Stuart Brittain; Miguel Fernandez-del-Olmo; Pilar Gomez-Garre; Pablo Mir; Ned Jenkinson; Binith Cheeran; Peter Brown (Experimental Brain Research, 2012)

Disruption of Saccadic Adaptation with Repetitive Transcranial Magnetic Stimulation of the Posterior Cerebellum in Humans - Ned Jenkinson; R. Chris Miall (The Cerebellum, 2010)

Adaptation to rotated visual feedback: a re-examination of motor interference - R. Christopher Miall; Ned Jenkinson; Kunal Kulkarni (Experimental Brain Research, 2004)